A study on knowledge quality and job performance of knowledge workers by analyzing content of social network sites using sentiment network analysis - Lim, Justin Renn Aun; Lee, Angela Siew Hoong *; Lim, Tong Ming * (International Foundation for Research & Development, 2013)
The importance of knowledge quality has become a key research area in recent research works. Many organizations realize that benefits of knowledge creation and sharing cannot be obtained unless quality of knowledge is achieved. This research investigates the perception of knowledge workers that uses social network sites as a means for social interaction, collaboration and knowledge sharing. The entries posted by these knowledge workers on the social network sites are gathered and studied with the presence of the element of sentiment such as emotion using sentiment network analysis. Based on the analysis, the results investigate the relationship between sentiment and quality of knowledge shared among knowledge workers on social networking sites and individual job performance. This research will analyse the improvements of employees’ job performance through the quality knowledge using interview, questionnaire survey, and text analysis to look for conversational patterns and element of sentiment. This research will investigate a number of knowledge driven companies that use social network sites. Structural Equation Modelling (SEM) is used to analyse responses collected from survey data.